Hunting in America : a novel - Hakimi, Tehila (Penguin Books, 2025)
"An Israeli woman relocates to America on assignment from her tech company. In an attempt to leave her past behind and adapt entirely to the new culture in which she finds herself, she joins her colleagues on a deer hunt, discovering a surprising acumen for the sport. She fires again and again, refining her skills with every shot. As she embarks on an affair with her hunting guide and colleague, David, she sinks deeper into hunting season, vacillating between predator and prey as the boundaries between man, woman, work, and nature begin to collapse. Hunting with David becomes the one stable aspect of her life until one day everything changes. With a poet's eye and a hunter's aim, Tehila Hakimi's beguiling debut novel is a taut, twisty story about the everyday violence that haunts countries, and one woman's tenuous grasp on reality"-- Provided by publisher.